Herbicida ácido 2,4-diclorofenoxiacético (2,4-D): investigação dos efeitos sobre o desenvolvimento, estresse oxidativo e parâmetros hepáticos em embriões e larvas de zebrafish (Danio rerio) - Martins, Rafael Xavier (2021)
The 2.4 dichlorophenoxyacetic acid (2,4-D) was one of the first synthetic herbicides to be introduced on the market and is currently the main ingredient of over 1500 commercially available products. Although 2,4-D is extensively used worldwide, several studies report that exposure to this chemical can induce toxic effects in non-target organisms. The liver is considered one of the targets of several toxicants because it performs a range of vital functions and directly participates in the metabolism of xenobiotics. Therefore, the present work aimed to understand the hepatotoxic potential of 2,4-D in zebrafish larvae (Danio rerio), as a contribution to the knowledge about the toxicity mechanisms of this chemical in a vertebrate model system. For this purpose, its acute toxicity to zebrafish embryos was assessed according to the OECD protocol No. 236 (2013), as well as its sub- lethal effects (<LC50) on the activity of enzymes related to oxidative and metabolic stress (LDH, GST, CAT and GPx) and hepatic damage (AST, ALT and ALP) after 48 h of exposure. Morphological analysis of the liver of treated larvae were also performed. We found that 2,4-D reduced larvae survival (LC50 15.010 mg/L in 96h of exposure), induced malformations, altered the activity of LDH, GST and CAT and significantly increased the activity of biomarkers for liver damage (AST, ALT and ALP). Although no morphological changes (relative color and size) in the larval liver were observed after 48 h of exposure, histopathological analysis revealed that treatment with 2,4-D causes severe changes in liver tissue, such as vacuolization of the cytosol, eccentric cell nucleus, as well as loss of tissue architecture and cell boundaries. Thus, our results show that 2,4-D alters the enzymatic profile for oxidative stress and shows hepatotoxic effects in zebrafish larvae.